Impact of Systematic Investment Plans on Retail Investor Wealth Creation: Evidence from Indian Mutual Funds - Prabha, P. V.; Radha, P. (Apex Journal of Business and Management, 2026)
Systematic Investment Plans (SIPs) have emerged as a popular investment mechanism among retail investors in India due to their simplicity, affordability, and disciplined approach to wealth creation. This study examines the impact of SIP investments on retail investor wealth creation by analyzing their performance across selected Indian mutual fund schemes. The research evaluates the effectiveness of SIPs in mitigating market volatility through rupee cost averaging and assesses long-term return potential compared to lump-sum investments. Secondary data from equity-oriented mutual funds over a multi-year period are analyzed using risk–return measures such as CAGR, standard deviation, and Sharpe ratio. The findings indicate that SIPs promote disciplined investing, reduce timing risk, and contribute significantly to long-term wealth accumulation for retail investors, especially during volatile market phases. The study highlights the suitability of SIPs for small and medium investors seeking sustainable financial growth and provides insights for policymakers and financial advisors in promoting informed investment behavior.